Water model study of the removal effect of soluble gas floatation technology (SGFT) on inclusions with different characteristics. (April 2021) - Zhang, Jie; Yan, Baijun; Liu, Jianhua; He, Yang; Li, Wei; Liu, Hongbo
Abstract: In this study, the removal effects of soluble gas floatation technology (SGFT) on inclusions with different characteristics were studied by using a self-made water model experimental device and Coulter counter. The water/CO2 system was used to simulate the molten steel/(H2, N2 ) system, and PP, PE and ABS particles were used to simulate the inclusions in molten steel. The experimental results show that this technology has good removal effects on particles with different characteristics. A large amount of fine bubbles can be formed when adding particles via heterogeneous nucleation, while no bubbles were formed without adding particles due to lack of nucleation cores. The removal rate of the particles increases with the increase of particle number. The size of the particles has a significant impact on its removal effect that the removal rate increases with the increase of particle size. The Ostwald ripening may appear on the bubble nucleation process on the surface of large particles, which can promote floating behavior and removal effect of the particles. The particles with different contact angles can be removed effectively by soluble gas floatation technology (SGFT), while the removal effect of particles with large contact angles is better. Highlights: Fine bubbles can be formed when adding particles via heterogeneous nucleation. SGFT has good removal effects on particles with different characteristics. The removal rate of the particles increases with the increase of particle number. The removal rate of the particles increases with the increase of particle size. The particles with large contact angles have a better removal effect.